Berberine Mediated Positive Inotropic Effects on Rat Hearts via a Ca2+-Dependent Mechanism - Zhao, Junli; Wang, Yaqian; Gao, Jie; Jing, Yang; Xin, Wenkuan (Frontiers in Pharmacology, 2020)
Previous studies showed that berberine, an alkaloid from Coptis Chinensis Franch, might exert a positive inotropic effect on the heart. However, the underlying mechanisms were unclear. Here, we reported that berberine at 10 - 20 µM increased the left ventricular developed pressure and the maximal rate of the pressure rising, and it increased the maximal rate of the pressure descending at 20 µM in Langendorff-perfused isolated rat hearts. These effects diminished with the concentration of berberine increasing to 50 µM. In the concentration range of 50 to 300 µM, berberine increased the isometric tension of isolated left ventricular muscle (LVM) strips with or without electrical stimulations, and it (30 - 300 µM) also increased the intracellular Ca2+ level in the isolated left ventricular (LV) myocytes. The removal of extracellular Ca2+ hindered the berberine-induced increases in the tension of LVM strips and the intracellular Ca2+ level of LV myocytes. These suggested that berberine might exert its positive inotropic effects via enhancing Ca2+ influx. The blockade of L-type Ca2+ channels (LTCCs) with nifedipine significantly attenuated 300 μM berberine-induced tension increase in LVM strips but not the increase in the intracellular Ca2+ level. Berberine (300 μM) further increased the LVM tension following the treatment with the LTCC opener FPL-64716 (10 μM), indicating an LTCC-independent effect of berberine. Lowering extracellular Na+ attenuated the berberine-induced increases in both the tension of LVM strips and the intracellular Ca2+ level of LV myocytes. In conclusion, berberine might exert a positive inotropic effect on the isolated rat heart by enhancing the Ca2+ influx in LV myocytes; these were extracellular Na+-dependent.